Do policies affect management? Evidence from a survey of clinicians of the Italian National Health Service. (February 2023) - Fattore, Giovanni; Numerato, Dino; Salvatore, Domenico
Since the early 1990s, New Public Management ideas have deeply influenced reforms and their implementation in the Italian NHS. We compare doctors' perceptions about management systems in two Italian regions which differ in the dominant values of the regional political environment. In total 220 doctors, orthopaedists and cardiologists, working in public hospitals in Lombardy and Emilia-Romagna, were surveyed. Doctors in Emilia-Romagna perceived their organization to be more managerially driven in comparison to their colleagues in Lombardy. Doctors from Lombardy perceived their professional freedom to be higher, regardless of their specialization. The divergence of professionals' perception between these two Italian regions, which operate within the same Beveridge model, shows that dominant values of regional politics may have tangible effects on hospital management.